Slick potassium channels limit TRPM3-mediated activation of sensory neurons - Engel, Patrick; Zhou, Fangyuan; Tran, Bang Tam Thi; Schmidtko, Achim; Lu, Ruirui (Frontiers in Pharmacology, 2024)
Heat sensation is mediated by specialized heat-sensitive neurons in the somatosensory system that innervates the skin. Previous studies revealed that noxious heat sensation is controlled by the sodium (Na+)-activated potassium (K+) channel Slick (Kcnt2), which is highly expressed in nociceptive Aδ-fibers. However, the mechanism by which Slick modulates heat sensation is poorly understood. Here, we generated mice lacking Slick conditionally in sensory neurons expressing Nav1.8 (SNS-Slick−/− mice). In SNS-Slick−/− mice, the latency to express any nocifensive behavior was reduced in the hot plate and tail immersion tests. In situ hybridization experiments revealed Slick was highly co-expressed with the essential heat sensor, transient receptor potential (TRP) melastatin (TRPM) 3, but not with TRP vanilloid 1, TRP ankyrin 1, or TRPM2 in sensory neurons. Notably, SNS-Slick−/− mice exhibited increased nocifensive behaviors following intraplantar injection of the TRPM3 activator pregnenolone sulfate. Patch-clamp recordings detected increased Na+-dependent outward K+ current (IK) after TRPM3 activation in sensory neurons, which showed no prominent IK after the replacement of NaCl with choline chloride. Thus, our study suggests that Slick limits TRPM3-mediated activation of sensory neurons, thereby inhibiting noxious heat sensing.